Ghrelin/GHS-R1A antagonism in memory test and its effects on central molecular signaling involved in addiction in rats - Lapka, Marek; Charalambous, Chrysostomos; Khryakova, Anna; Certilina, Alina; Novotny, Jiri; Hejnova, Lucie; Sustkova-Fiserova, Magdalena (Pharmacology, biochemistry, and behavior, 2023)
Central ghrelin signaling seems to play important role in addiction as well as memory processing. Antagonism of the growth hormone secretagogue receptor (GHS-R1A) has been recently proposed as a promising tool for the unsatisfactory drug addiction therapy. However, molecular aspects of GHS-R1A involvement in specific brain regions remain unclear. The present study demonstrated for the first time that acute as well as subchronic (4 days) administration of the experimental GHS-R1A antagonist JMV2959 in usual intraperitoneal doses including 3 mg/kg, had no influence on memory functions tested in the Morris Water Maze in rats as well as no significant effects on the molecular markers linked with memory processing in selected brain areas in rats, specifically on the β-actin, c-Fos, two forms of the calcium/calmodulin-dependent protein kinase II (CaMKII, p-CaMKII) and the cAMP-response element binding protein (CREB, p-CREB), within the medial prefrontal cortex (mPFC), nucleus accumbens (NAc), dorsal striatum, and hippocampus (HIPP). Furthermore, following the methamphetamine intravenous self-administration in rats, the 3 mg/kg JMV2959 pretreatment significantly reduced or prevented the methamphetamine-induced significant decrease of hippocampal β-actin and c-Fos as well as it prevented the significant decrease of CREB in the NAC and mPFC. These results imply, that the GHS-R1A antagonist/JMV2959 might reduce/prevent some of the memory-linked molecular changes elicited by methamphetamine addiction within brain structures associated with memory (HIPP), reward (NAc), and motivation (mPFC), which may contribute to the previously observed significant JMV2959-induced reduction of the methamphetamine self-administration and drug-seeking behavior in the same animals. Further research is necessary to corroborate these results.
Keywords: JMV2959; pCREB; Receptors, Ghrelin; c-Fos; β-Actine; aktiny; Intravenous self-administration/IVSA; krysa rodu Rattus; zvířata; Calcium-Calmodulin-Dependent Protein Kinase Type 2; methamfetamin; ghrelin; receptory ghrelinu; CaMKII; Ghrelin; GHS-R1A antagonism; Rats; Actins; proteinkinasa závislá na vápníku a kalmodulinu typ 2; Memory; Animals; CREB; Addiction; Methamphetamine